2018
DOI: 10.2174/1389203719666171213114919
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Control of Protein Solution by Small Solutes: A Review

Abstract: Viscosity of protein solution is one of the most troublesome issues for the high-concentration formulation of protein drugs. In this review, we summarize the practical methods that suppress the viscosi-ty of protein solution using small molecular additives. The small amount of salts decreases the viscosity that results from electrostatic repulsion and attraction. The chaotrope suppresses the hydrophobic attraction and cluster formation, which can lower the solution viscosity. Arginine hydrochloride (ArgHCl) al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 124 publications
2
69
0
Order By: Relevance
“…It is well documented that hydrophobic effect is an important phenomenon that drives the interaction between proteins which stabilizes the protein conformation. [ 67 ] Hence, it is logical that GelMA-Tyr, which is more hydrophobic thanGelMA, has an increased interaction between the macromer chains and thus requires a higher yield stress to facilitate extrusion of the material. Importantly, ACPCs were able to withstand the shear stress during extrusion where cell-laden GelMA or GelMA-Tyr bionks showed high cell viability (>70%, Figure 4B ) and sustained metabolic activity ( Figure S7, Supporting Information ) 1 and 7 days postprinting, demonstrating the suitability of the dual functionalized bioinks for applications in such a bioprinting approach.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that hydrophobic effect is an important phenomenon that drives the interaction between proteins which stabilizes the protein conformation. [ 67 ] Hence, it is logical that GelMA-Tyr, which is more hydrophobic thanGelMA, has an increased interaction between the macromer chains and thus requires a higher yield stress to facilitate extrusion of the material. Importantly, ACPCs were able to withstand the shear stress during extrusion where cell-laden GelMA or GelMA-Tyr bionks showed high cell viability (>70%, Figure 4B ) and sustained metabolic activity ( Figure S7, Supporting Information ) 1 and 7 days postprinting, demonstrating the suitability of the dual functionalized bioinks for applications in such a bioprinting approach.…”
Section: Resultsmentioning
confidence: 99%
“…The high solubility of albumin (up to 40% w / v ) at pH 7.4, its stability at pH values of 4 to 9, and temperature variations (up to 60 °C when heated for 10 h) without any deleterious effects make it an attractive macromolecular stabilizer [ 22 , 23 , 24 , 25 ]. As an example, Chang and co-workers demonstrated that BSA was able to stabilize an enzyme by promoting hydrophobic interactions and increasing the viscosity of the enzyme solution [ 26 ]; however, this must be carefully balanced as increasing the protein concentration and viscosity increases the probability of aggregation which could lead to decreased enzyme availability or non-uniform NP formation [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several types of protein-excipient interactions (hydrogen bonding, preferential hydration, electrostatic interactions, dispersive interactions, cationep interactions) could each effectively disrupt the PPIs within proteins. 37,38 Although TMPAI and TrpNH 2 HCl have the potential for pep interactions (via their aromatic rings interacting with aromatic rings in amino acid residues in mAb-C), GdnHCl, as a chaotropic salt, 39 was more effective in terms of diminishing PPIs for mAb-C. 40 Preferential interactions of GdnHCl with mAb-C might more effectively compete PPIs. 38 However, comparisons are complicated because I À from TMPAI is a stronger chaotrope than Cl À .…”
Section: Effects Of Hydrophobic (Tmpai and Trpnh 2 Hcl) And Chaotropimentioning
confidence: 99%
“…37,38 Although TMPAI and TrpNH 2 HCl have the potential for pep interactions (via their aromatic rings interacting with aromatic rings in amino acid residues in mAb-C), GdnHCl, as a chaotropic salt, 39 was more effective in terms of diminishing PPIs for mAb-C. 40 Preferential interactions of GdnHCl with mAb-C might more effectively compete PPIs. 38 However, comparisons are complicated because I À from TMPAI is a stronger chaotrope than Cl À . 41 Therefore, albeit similar properties exist between cations of TMPAI and TrpNH 2 HCl, the anions of these 2 additives, including I À and Cl À , may play roles that differentiate their RSA-disrupting efficiency.…”
Section: Effects Of Hydrophobic (Tmpai and Trpnh 2 Hcl) And Chaotropimentioning
confidence: 99%